Comparative and transnational dispute resolution - Advances in Comparative and Transnational ADR: Research into Practice (Conference) (2019 : University of Hong Kong Faculty of Law); Ali, Shahla F. (New York: Routledge, 2023)
'This edited volume presents research and policy insights into the theory and practice of dispute systems reform in diverse jurisdictions. It highlights how important extra-judicial mechanisms are for resolving cross border disputes, as evidenced both by the breadth of scholarship dedicated to the issue and proliferation of parties resorting to non-litigious dispute resolution mechanisms in recent years. Drawing on selected case studies, the book examines the impact of comparative research and policy analysis in advancing reform of dispute resolution institutions at both the regional and global levels. It explores the challenges and opportunities of understanding and assessing developments in systems of dispute resolution in diverse social and political contexts through comparative research. With growing number of disputes which have come to involve cross-border issues, anyone interested in transnational and comparative dispute resolution will find this book a useful reference'--
Introduction -- Shahla ALI, Introduction -- Matthew S. Erie, The problem of method in the study of transnational dispute resolution -- Michael Palmer, Modes of dispute resolution : exploring issues in the range -- Shahla Ali, Advancing research and practice in the governance of dispute resolution institutions through inclusive devolved reflection -- Michal Alberstein, Comparative Judicial Conflict Resolution (JCR) : between summary trials and ADR -- Lola Akin Ojelabi, The challenges of developing global ethical standards for mediation practice -- Nadja Alexander, International comparative mediation law : Hong Kong and Singapore in perspective -- Luiji Cominelli, Eleonora Ciscato, Stefania Lattuille, Environmental mediation and facilitation in Italy : theoretical insights and practical experience on non-adjudicative mechanisms and'total conflicts' -- Xianto Wen (with an introduction by Susan Finder), Comparative analysis of the Singapore Convention in light of the New York and Hague Choice of Court Conventions -- Xin He, Yang Se, Flexibility and authority : keys for informal justice to succeed -- Kwai Hang NG, Wearing two hats : problems of'in-trial' mediation in China -- Ling Zhou, Thinking about consumer mediation in China : some examples from Shenzhen.
Includes bibliographical references and index. (254-257 pages)
Puan Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 6393/ Pemilihan Ketua Perpustakaan Undang-Undang/ CIP/ Bookline Services
Keywords: Dispute resolution (Law) -- Congresses; International commercial arbitration -- Congresses; International business enterprises -- Law and legislation -- Congresses